La falta de proporcionalidad para las sanciones de las infracciones establecidas en el Art. 145. literal C respecto al literal A de la Ley Orgánica de Transporte Terrestre, Tránsito y Seguridad Vial, del Juzgado Sexto de Garantías Penales y de Tránsito de El Oro - Beltrán Zambrano, Flavio Antonio (2013)
In this thesis an analysis of very serious infringements contained in Art will be held. 145 letters a) and c) of the Organic Law of Land Transportation, Traffic and Road Safety which is punishable by imprisonment for three days without having obtained the license driver and a penalty imprisonment three days without obtaining a driver's license and a penalty of minimum two basic remuneration mininas unified worker in general and retention vehicle for up to seven days to who would result a vehicle with a license in a different category the payable for the vehicle that is driving.